STRATEGIC RESOURCE MANAGEMENT: FIXING THE MISSING CHAIN IN THE COMMERCIALIZATION OF UZBEK UNIVERSITY RESEARCHES - Ismoilov Elyorjon Makhamadali Ugli (TADQIQOTLAR, 2026)
Abstract. The study investigates the strategic resource management of academic intellectual property, aiming to explore the transition mechanisms for the commercialization of university researches in the Republic of Uzbekistan. By utilizing the Resource-Based View (RBV) logic and qualitative assessment of the VRIO framework, the analysis reveals a significant gap in the strategic orchestration of academic knowledge, but exposes an “innovation productivity paradox” in the emerging digital economy. The high concentration of raw scientific publications is negatively correlated with actual startup ecosystem integration, reflecting the dominance of isolated academic practices over market-driven innovation. Besides, institutional landscapes revealed a critical deficit in the organizational capacity necessary to exploit valuable resources. To meet the ambitious targets of the “Digital Uzbekistan - 2030” strategy, there is a necessity of fixing the “missing chain”- specifically, intermediary technology transfer mechanisms-extracting crucial lessons from strategic resource orchestration to transform academic potential into sustained competitive advantage.